A multi‐scale framework for flood risk analysis at spatially distributed locations. Issue 1 (18th September 2015) - Speight, L.J.; Hall, J.W.; Kilsby, C.G.
Abstract: This paper presents a multi‐scale framework for flood risk analysis from fluvial and coastal sources at broad (including national) scales. The framework combines an extreme value spatial model of fluvial and coastal flood hazards using the Heffernan and Tawn conditional dependence model, with a new Markov approach to representing the spatial variability of flood defences. The nested multi‐scale structure enables spatial and temporal dependence at a national scale to be combined with detailed local analysis of inundation and damage. By explicitly considering each stage of the process, potential uncertainties in the risk estimate are identified and can be communicated to end users to encourage informed decision making. The framework is demonstrated by application to an insurance portfolio of static caravan sites across the UK worth over £2bn. In the case study, the largest uncertainties are shown to derive from the spatial structure used in the statistical model and limited data on flood defences and receptor vulnerability.